Kontrol Gerak Robot Lengan Menggunakan Handphone - Ariyono SE (Jurnal Penelitian)
At this time the development and technological advances encourage the people to change the ordinary life style extra ordinary life style, sophisticated, modern, and still give priority to security that become relatively high. Therefore human is required in order to adapt twith the condition that exist at this time. One of them is the development in the robotics world. Because the benefits of robot is very important in helping the human job or replace the role of humans life, either in industry or in other sector that have a control system respectively. Therefore designed a robot arm control system using a communication device that is familiar and almost every people use it. That is a handphone. The working principle of that device a command or input from handphone then transmitted to electronic circuit that used bluetooth media. There is also bluetooth at the circuit that work to continue use data or command from handphone. On microcontroller using IC ATMEGA 16 and the programing language C. From the microcontroller has set the motor DC on robot arm. Which will be driveraccording with instruction that given by that handphone